An Intruder in the Discourse of Reality: Dream in The Peony Pavilion and Dream of the Red Chamber - Espinosa-Campos, Lucía (Sinología hispánica. China Studies Review, 2026)
This article compares the role of dreams in the classic Chinese literary works The Peony Pavilion and Dream of the Red Chamber, uncovering recurrent patterns in the representation of dreams. Through the identification, enumeration, and description of similar patterns in dream intervention in both works, a systematic analytical method is proposed to recognize and understand these traits, as well as their impact on the overall narrative of each work. By analyzing the influence of dreams on discourse, characters, and plot development, the study explores whether these dreams follow a specific mechanism and whether they can be systematized. From a critical perspective within the field of Sinology, this study aims to establish a solid foundation for understanding dreams in The Peony Pavilion and Dream of the Red Chamber, revealing the symbolic and narrative richness of these dream elements in classical Chinese literature.